Penguatan Pendidikan Karakter di Era Industri 4.0: Optimalisasi Pendidikan Agama Islam di Sekolah - Kosim, Muhammad (TADRIS: Jurnal Pendidikan Islam, 2020)
Advances in information and communication technology in the Digital Revolution Era, in addition to positive impacts, also had a negative impact on human character, such as individualist, materialist attitudes, and even rejecting spiritual aspects. Therefore, we need the concept of Strengthening Character Education by optimizing the role of Islamic Religious Education in Schools to educate students who have faith, taqwa, and have good character according to their fitrah. To answer this need, a library research study was conducted which analyzed several papers that were relevant to the hermeneutic approach and content analysis method. This article finds that the optimization of Islamic Religious Education in Strengthening of Character Education in schools can be done by: first, strengthening the character of Muslim teachers who emulate the character of the Prophet SAW as a true educator; secondly, optimization of Islamic Religious Education in Class-based Strengthening Character Education with a tauhid-based science paradigm, integrating Islamic values in learning, and strengthening Islamic Religious Education materials in schools; third, optimization of Islamic Religious Education in school-based Strengthening Character Education by implementing the concept of taqwa-based Islamic education and making surau as a character labor; and fourth, the optimization of Islamic Religious Education in community-based Strengthening Character Education by organizing Islamic parenting and school collaboration with parents and the community in strengthening the character of students.